Does hookah smoking carry less cardiovascular risks than cigarette smoking in patients presenting with myocardial infarction? - Turki B Albacker; Rakan Barghouthi; Ibrahim Al Fawaz; Yazeed Al Saadan; Mahmood Tokhta; Abdulaziz Alkorbi; Sayed Abou Almakarem; Moustafa Refaie; Khalid Eskandar (Wolters Kluwer Medknow Publications, 2020)
Introduction: Smoking is an important risk factor for cardiovascular diseases. There is an increase in the prevalence of hookah smoking in both genders and among all age groups in Saudi Arabia with the misconception that hookah smoking carries less risk than cigarette smoking.Objective: Our aim in this study was to compare the outcomes of hookah versus cigarette smoking in patients presenting with myocardial infarction (MI). Methodology: In this retrospective study, we included 246 patients who presented with MI between May 2014 and October 2016. The prevalence of smoking was 56.5% in this group. The smokers were divided into two groups: hookah smokers and cigarette smokers. Propensity matching was performed to control for differences in patients' characteristics. The outcomes of in-hospital mortality, number of diseased vessels, type of intervention, and recurrence of ischemia were compared between the two groups. Results: Among the 139 smokers, 35 were hookah smokers (25%) and 104 were cigarette smokers (75%). The median number of cigarettes or cigarette equivalent per day was similar between the two groups (20). Both groups had similar outcomes in the number of diseased vessels, type of intervention, recurrence of symptoms, and mortality (hookah = 4.9% and cigarettes = 2.9%, P = 1). Conclusion: These findings support the fact that hookah smoking carries the same harmful effect as cigarette smoking on patients with MI and that the risk might be related to the number of cigarettes smoked per day rather than the type of smoking.